Abundance and spatial distribution of marine debris on the beach of Takalar Regency, South Sulawesi. Issue 1 (May 2021) - Faizal, A.; Werorilangi, S; Samad, W; Lanuru, M; Dalimunte, W S; Yahya, A
Abstract: This study aimed to map the spatial distribution of marine debris abundance in the beach area of Takalar Regency, South Sulawesi Province, Indonesia. This research was conducted during the east monsoon in August-September 2019 and July-August 2020. The data were collected from the beach of Takalar at 2 stations; station 1 in Punaga River Estuary and station 2 in Laikang Bay, with 3 replications per station. Sampling was carried out using the transect method, the length of the transect line is 100 meters parallel to the coastline. Samples were collected within the criteria of macro size (> 2.5 cm - 1 m) and meso size (> 5 mm - 2.5 cm). The results showed that the average total abundance of marine debris in the macro size category was 0.036 items/m 2 and in the meso size was 0.0012 items/m 2 ; while the average weight abundance of macro and meso marine debris respectively were 0.36 g/m 2 and 0.0013 g/m 2 . The spatial distribution showed that the greatest abundance of macro and meso waste was found at station 2 or around Laikang Bay. The semi-enclosed water in Laikang Bay is linked to the high accumulation of debris in the location.